If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 1) = 100 Reorder the terms: x(1 + x) = 100 (1 * x + x * x) = 100 (1x + x2) = 100 Solving 1x + x2 = 100 Solving for variable 'x'. Reorder the terms: -100 + 1x + x2 = 100 + -100 Combine like terms: 100 + -100 = 0 -100 + 1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '100' to each side of the equation. -100 + 1x + 100 + x2 = 0 + 100 Reorder the terms: -100 + 100 + 1x + x2 = 0 + 100 Combine like terms: -100 + 100 = 0 0 + 1x + x2 = 0 + 100 1x + x2 = 0 + 100 Combine like terms: 0 + 100 = 100 1x + x2 = 100 The x term is 1x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. x + 0.25 + x2 = 100 + 0.25 Reorder the terms: 0.25 + x + x2 = 100 + 0.25 Combine like terms: 100 + 0.25 = 100.25 0.25 + x + x2 = 100.25 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 100.25 Calculate the square root of the right side: 10.012492197 Break this problem into two subproblems by setting (x + 0.5) equal to 10.012492197 and -10.012492197.Subproblem 1
x + 0.5 = 10.012492197 Simplifying x + 0.5 = 10.012492197 Reorder the terms: 0.5 + x = 10.012492197 Solving 0.5 + x = 10.012492197 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 10.012492197 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 10.012492197 + -0.5 x = 10.012492197 + -0.5 Combine like terms: 10.012492197 + -0.5 = 9.512492197 x = 9.512492197 Simplifying x = 9.512492197Subproblem 2
x + 0.5 = -10.012492197 Simplifying x + 0.5 = -10.012492197 Reorder the terms: 0.5 + x = -10.012492197 Solving 0.5 + x = -10.012492197 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -10.012492197 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -10.012492197 + -0.5 x = -10.012492197 + -0.5 Combine like terms: -10.012492197 + -0.5 = -10.512492197 x = -10.512492197 Simplifying x = -10.512492197Solution
The solution to the problem is based on the solutions from the subproblems. x = {9.512492197, -10.512492197}
| 6x+9=4x+57 | | 6x-(4x-8)=24 | | 0.15x+2=x | | -6b-2b=-16 | | 5(2x-1)=44 | | -4(x-6)=-40 | | 22m*2=3x | | 5-(-2-3p)-(-3+4p)=2-(p-4)-(-3p+2) | | (-5u^3v^4+9u)+(-5u^3-8u+8u^2v^2)+(-8u^4v^2+8u^3v^4)= | | (-x^4+13x^5+6x^3)-(6x^3+5x^5+7x^4)= | | 22m^2=.5(3x-1) | | x+1.5x=80 | | 22m^2=.5(3x-1)(x) | | 9x+8=7x+28 | | 22m^2=.5(3-1) | | m^2=3x | | 22m^2=3x | | 3x-1(x)=22m^2 | | 3x-1=22m^2 | | 4x-16y=16 | | .3(3)-1=x | | -8(t-6)-(t+8)=1 | | 12x+12=10+12x | | 3x-1=b | | (.5)(3x-1)(x)=m | | (x-7)(x^2-5x+2)= | | x(3x-1)=m | | 3x-1=m | | 22m^2=x | | 6-8a-16=8+a | | 2m-8+5=4m-11 | | h(t)=16t^2+160t |